United Notation 2030 Agenda for Sustainable Development Goals: Appraisal and Prospects - Saleh, Mohammed M. (European Journal of Economics and Business Studies, 2017)
United Nations adopted in 2015 seventeen Sustainable Development Goals to be achieved in 2030.The main goals are: ending poverty, ending hunger, achieving equity in heath, education, water treatment and sanitation, full and productive employment for all, sustainable economic growth, sustainable consumption and production pattern, combat climate change and other environmental goals. There are many constraints encountering the achievements of these goal.These constraints are basically financial and political. This paper emphasizes that these goals cannot be achieved without large scale of international financial support in term of grants and easy term loans. In addition, UN has to play its role in preserving international peace and security which are the basic elements in sustainable development. Time frame for achieving sustainable development goals should be extended ,probably, to the mid of this century.